Applicability Of Gestalt Theory In Glogster - Ziaee, Anika (2011)
The study was aimed at identifying one of the social networks website and its efficiency of developing learning and engaging the students and improving their knowledge. By doing so, to better understand the practice of Glogster social network within a shared knowledge environment, it is essential to study students perception of using Glogster and their perception of applicability of gestalt theory via this social networking tool.